Statin therapy prescribing for patients with type 2 diabetes mellitus: A review of current evidence and challenges - Mohamed Hassan Elnaem; Mohamad Haniki Nik Mohamed; Hasniza Zaman Huri; Shah M Azarisman; Ramadan Mohamed Elkalmi (Wolters Kluwer Medknow Publications, 2017)
Use of statin therapy in patients with type 2 diabetes mellitus (T2DM) has been recommended by most clinical guidelines. Cardiovascular disease (CVD) is a leading cause of morbidity and mortality among T2DM patients. It has been proved that statins are effective for primary or secondary CVD prophylaxis. Reports have highlighted the underutilization of statins in clinical practice and the suboptimal adherence to guideline recommendations. This review article points to summarize the current evidence confirming the role of statins in T2DM patients and to provide an overview of factors that may affect statins' prescribing patterns and compliance in clinical practice. Initiatives to enhance statin therapy prescribing should recognize the comprehensive nature of the prescribing process. Attempts to assure proper statin prescribing and utilization can help in achieving better clinical outcomes of statin therapy.